(untitled) (International Journal of Technology and Management Research, 2020)
Shopping for souvenir is an important aspect of the tourism activity which almost all tourists participate in. The purpose of this paper is to examine the expenditure pattern of international tourists on souvenirs in Accra. The study adopted the descriptive design and questionnaire was administered to gather data. Data collected from 196 international tourists who were sampled from hotspots in Accra, using convenient sampling method, revealed that there was a significant relationship between socio-demographic characteristics of tourists and expenditure on souvenirs. Therefore, socio-demographic characteristics of an individual was found to have likely influence on the individual’s expenditure on souvenirs. Also, a majority of the respondents, who were first time visitors, spent less on souvenirs. A significant average expenditure on souvenirs signifies that the souvenirs business is a profitable business that needs to be maintained and enhanced. Majority of the respondents had souvenirs as part of their purchase plans. Leisure travellers were noted to spend more on souvenirs than other travellers. Souvenir shopping generates a good amount of money and as such the Centre for National Culture and Ghana Tourism Authority should embark on activities aimed at packaging and promoting the arts and crafts of the country so as to arouse sales of souvenirs. Keywords: Souvenirs, Arts and Crafts, Tourists, Expenditure, Purchase